The impact of managerial behaviour on employees' perfomance: A case study of the Coca-Cola Bottling Company of Ghana Limited-Kumasi Plant - Kumah, Evelyn (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration, May-2009